The semantics of spatial prepositions: the main trends of research - Stasiūnaitė, Ieva (Taikomoji kalbotyra, 2016)
The paper overviews the main trends of research into the semantics of spatial prepositions, as demonstrated by a plethora of papers on linguistic data from a variety of languages. The more traditional approach focuses on the locative meaning with respect to other words—both syntagmatically and in paradigms, thus ruling out pragmatics—and considers multiple senses of the same preposition to be arbitrary. In contrast, the modern framework employs the principles of cognitive linguistics for semantic analysis, highlighting the conceptual structuring of entities or relations in extralinguistic reality. On the basis of geometric, functional, and other relations between the figure and the ground, it attempts to explicate not only prepositional synonymy, but also extensive polysemy as a form of categorisation. As a consequence, the distinct meanings of a preposition are considered to be related, deriving either from the prototypical sense or any other sense which is related to it, and arranged in a network. The modern line of investigation may provide more possibilities for researchers interested in one language and/or in cross-linguistic studies, thus contributing to the development of lexicography, translation, and other fields of applied linguistics.
Keywords: prepositions; semantics; polysemy; synonymy; cognitive linguistics; structuralism